The efficacy of peroral cholangioscopy for difficult bile duct stones and indeterminate strictures: a systematic review and meta-analysis - Korrapati, Praneet; Ciolino, Jody; Wani, Sachin; Shah, Janak; Watson, Rabindra; Muthusamy, V. Raman; Klapman, Jason; Komanduri, Srinadh (Endoscopy International Open, 2016)
Background and study aims: Current evidence supporting the efficacy of peroral cholangioscopy (POC) in the evaluation and management of difficult bile duct stones and indeterminate strictures is limited. The aims of this systematic review and meta-analysis were to assess the following: the efficacy of POC for the therapy of difficult bile duct stones, the diagnostic accuracy of POC for the evaluation of indeterminate biliary strictures, and the overall adverse event rates for POC.Patients and methods: Patients referred for the removal of difficult bile duct stones or the evaluation of indeterminate strictures via POC were included. Search terms pertaining to cholangioscopy were used, and articles were selected based on preset inclusion and exclusion criteria. Quality assessment of the studies was completed with a modified Newcastle-Ottawa Scale. After critical literature review, relevant outcomes of interest were analyzed. Meta-regression was performed to examine potential sources of between-study variation. Publication bias was assessed via funnel plots and Egger’s test.Results: A total of 49 studies were included. The overall estimated stone clearance rate was 88 % (95 % confidence interval [95 %CI] 85 % – 91 %). The accuracy of POC was 89 % (95 %CI 84 % – 93 %) for making a visual diagnosis and and 79 % (95 %CI 74 % – 84 %) for making a histological diagnosis. The estimated overall adverse event rate was 7 % (95 %CI 6 % – 9 %).Conclusions: POC is a safe and effective adjunctive tool with endoscopic retrograde cholangiopancreatography (ERCP) for the evaluation of bile duct strictures and the treatment of bile duct stones when conventional methods have failed. Prospective, controlled clinical trials are needed to further elucidate the precise role of POC during ERCP.